2022
DOI: 10.3389/fnut.2022.982370
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of starch-based functional food nano-microcapsule delivery system and its controlled release characteristics

Abstract: Most of the functional substances in food are absorbed in the small intestine, but before entering the small intestine, the strong acid and enzymes in the stomach limit the amount that can reach the small intestine. Therefore, in this paper, to develop a delivery system for functional food ingredients, maintain the biological activity of the ingredients, and deliver them to the target digestive organs, preparation of starch-based functional food nano-microcapsule delivery system and its controlled release char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Nanoencapsulation based on pectin has attracted attention due to favorable properties, such as large specific surface area, excellent stability, good biocompatibility, improved permeability and retention time of the encapsulated compound, uncomplicated design and preparation, structural flexibility and preferred characteristics of controlled release in the intestine, and delivery to specific physiological sites ( 210–212 ). In addition, the nanoencapsulation process contributes to improved antioxidant properties and prebiotic effects ( 213 ).…”
Section: Biomaterials For Elaborating Nanostructure Systems For Encap...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoencapsulation based on pectin has attracted attention due to favorable properties, such as large specific surface area, excellent stability, good biocompatibility, improved permeability and retention time of the encapsulated compound, uncomplicated design and preparation, structural flexibility and preferred characteristics of controlled release in the intestine, and delivery to specific physiological sites ( 210–212 ). In addition, the nanoencapsulation process contributes to improved antioxidant properties and prebiotic effects ( 213 ).…”
Section: Biomaterials For Elaborating Nanostructure Systems For Encap...mentioning
confidence: 99%
“…At neutral pH, the carboxylic acid (pKa pH ~3.6) has a net negative charge interacting with cationic molecules (proteins and polysaccharides) to form nanocomplexes ( 8 ). Pectins have the property of interacting with certain types of proteins at variable pH, stabilizing the nanostructures formed in acid or neutral dispersions ( 8 , 213 ).…”
Section: Nanocarriers Based On Natural Polysaccharides: the Promising...mentioning
confidence: 99%
“…However, the small molecules included by starch have problems such as a low embedding rate and insufficient embedding. Zhang et al [ 10 ] and Tian et al [ 11 ] have reported that ultrasound can improve the ability of starch to include small molecules. Furthermore, the use of ultrasonication for the preparation of inclusions is a well–established method [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Porous starch is a kind of modified starch, formed by amylase at a temperature lower than gelatinisation, with the advantages of safety, easy access and environmental friendliness (Gao et al ., 2013). Porous starch has a porous honeycomb like structure, which is also an ideal material for probiotic embedding to improve its gastrointestinal tolerance (Tian et al ., 2022). For example, the viable counts of Lactiplantibacillus plantarum 299v encapsulated with porous corn starch was significantly higher than that of free bacteria after acid treatment, which improved by about 21.5% (Li et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%